Wearable wireless sensor for real-time angle measurements - Sabti, H. A.; Thiel, D. V. (Journal of Fitness Research, 2016)
Wearable sensors provide an easy solution for capture and processing athlete movements while eliminating the need for wired connections. This paper reports a new approach for limb rotation and angle measurements through the use of a 2.45 GHz wireless accelerometer sensor, by measuring the tilt angle as function of gravitational acceleration. The acceleration values were normalized and mapped to calculate angle measurements with prediction accuracy of 5°. This type of measurements can play a significant role in the process of athlete rehabilitation, such as, restoring the full range of movement for ankle sprain injuries.